Aberrant tryptophan metabolism in stromal cells is associated with mesenteric fibrosis in small intestinal neuroendocrine tumors. Issue 4 (29th April 2022) - Blažević, Anela; Iyer, Anand M; van Velthuysen, Marie-Louise F; Hofland, Johannes; van Koestveld, Peter M; Franssen, Gaston J H; Feelders, Richard A; Zajec, Marina; Luider, Theo M; de Herder, Wouter W; Hofland, Leo J
Abstract : Background: Increased levels of serotonin secretion are associated with mesenteric fibrosis (MF) in small intestinal neuroendocrine tumors (SI-NETs). However, the profibrotic potential of serotonin differs between patients, and in this study, we aimed to gain an understanding of the mechanisms underlying this variability. To this end, we analyzed the proteins involved in tryptophan metabolism in SI-NETs. Methods: Proteomes of tumor and stroma from primary SI-NETs and paired mesenteric metastases of patients with MF ( n   = 6) and without MF ( n   = 6) were identified by liquid chromatography–mass spectrometry (LC-MS). The differential expression of proteins involved in tryptophan metabolism between patients with and without MF was analyzed. Concurrently, monoamine oxidase A (MAO-A) expression was analyzed in the tumor and stromal compartment by immunohistochemistry (IHC) and reported as intensity over area (I/A). Results: Of the 42 proteins involved in tryptophan metabolism, 20 were detected by LC-MS. Lower abundance of ten proteins was found in mesenteric metastases stroma in patients with MF. No differential expression was found in primary SI-NETs. In patients with MF, IHC showed lower MAO-A expression in the stroma of the primary SI-NETs (median 4.2 I/A vs 6.5 I/A in patients without MF, P  = 0.003) and mesenteric metastases (median 2.1 I/A vs 2.8 I/A in patients without MF, P = 0.019). Conclusion: We found a decreased expression of tryptophan and serotonin-metabolizing enzymes in the stroma in patients with MF, most notably in the mesenteric stroma. This might account for the increased profibrotic potential of serotonin and explain the variability in the development of SI-NET-associated fibrotic complications.